2008
DOI: 10.1021/ja806284x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration IndexA Better Parameter for Explaining Small Molecule Hydration in Inhibition of Ice Recrystallization

Abstract: Several simple mono- and disaccharides have been assessed for their ability to inhibit ice recrystallization. Two carbohydrates were found to be effective recrystallization inhibitors. D-galactose (1) was the best monosaccharide and D-melibiose (5) was the most active disaccharide. The ability of each carbohydrate to inhibit ice growth was correlated to its respective hydration number reported in the literature. A hydration number reflects the number of tightly bound water molecules to the carbohydrate and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
137
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(151 citation statements)
references
References 52 publications
10
137
2
2
Order By: Relevance
“…Ben et al have developed a series of short glycopeptides that have specific IRI activity at very low concentrations. These analogues have been showed to be more synthetically accessible, biocompatible with human embryonic liver (WRL-68) cells and shown marginal benefits when added into standard cryopreservation solutions 28,29 . These peptides have also been shown to be readily internalized, making their post-thaw removal non-trivial.…”
mentioning
confidence: 99%
“…Ben et al have developed a series of short glycopeptides that have specific IRI activity at very low concentrations. These analogues have been showed to be more synthetically accessible, biocompatible with human embryonic liver (WRL-68) cells and shown marginal benefits when added into standard cryopreservation solutions 28,29 . These peptides have also been shown to be readily internalized, making their post-thaw removal non-trivial.…”
mentioning
confidence: 99%
“…[85] Further modulation of the properties of these mimics could be delivered by increasing the hydrophobicity of the backbone through the preparation of the corresponding Xaa-Ala-Ala/Xaa-Val-Val mimics. The strong correlation between the hydration index and RI activity also suggests that glycoconjugates of melibiose, which was measured as containing the highest hydration index, [83] can deliver even more potent compounds. Finally, the ability to predict whether a designed molecule is likely to exhibit antifreeze activity would be extremely useful.…”
Section: Discussionmentioning
confidence: 93%
“…In order to further fine-tune the RI activity, the hydration index was developed as a general method aimed at assessing the degree of hydration of carbohydrates. [83] The hydration index was shown to correlate well with RI activity for a range of mono-and disaccharides, with the C-linked derivatives of the monosaccharides having comparable activity to the corresponding O-linked monosaccharides.…”
Section: Glycoconjugate Derivatives Of Xaa-gly-glymentioning
confidence: 93%
“…b-PMP-Glc (6) also exhibited comparable IRI activity to a 220 mM solution of sucrose, which is a common ingredient of many cryopreservation solutions 28 . Our laboratory has previously correlated IRI activity to carbohydrate hydration and reported that glycoconjugates containing highly hydrated monosaccharides (such as D-galactose) were more IRI active than those containing less hydrated monosaccharides (D-glucose and D-mannose) 23,43 . This trend was also observed in small molecules where the non-ionic pyranose-based surfactants containing a highly hydrated D-galactose head group (b-Octyl-Gal, 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first example where a glucopyranose derivative is significantly more IRI active than a galactopyranose derivative. It was also surprising that both b-PMP-Gal (5) and b-PMP-Man (7) exhibited identical IRI activities despite the difference in hydration between these two pyranose residues 23,43,44 . Unfortunately, hydration numbers or molar compressibilities of 5-7 have not been reported in the literature, thus a correlation between the hydration characteristics of these compounds and their IRI activity is not possible at this time.…”
Section: Resultsmentioning
confidence: 99%